The theoretical study of temperature- and pressure-dependent reactions kinetic for unimolecular isomerization reactions of C2H5O radical - Tri, Nguyen Ngoc; Ha, Nguyen Ngoc (Vietnam Journal of Chemistry, 2016)
Minimum energies for the C2H5O radical, products and transition states of reactions on the potential energy surface were obtained at the MP2/6-311++G(3df,2pd) high level of theory, and single-point energies were refined at the CCSD(T)/6-311++G(3df,2pd) level of theory for all stationary points. Isomerization reactions of C2H5O radical take place via two proton migration mechanisms: C2H5O → CH3CHOH (1,2-H shift) (1) and C2H5O → CH2CH2OH (1,3-H shift) (2). Temperature and pressure-dependent rate constants of the two reactions (1) and (2) were calculated by using transitional state theory (TST) and Rice-Ramsperger-Kassel-Marcus (RRKM) theory. Obtained results show that the reaction rate constants were: k∞TST(T) (1) = 1.978.1010.T0.428 exp(-13530.4/T), k∞TST(T) (2) = 3.077.1010.T0.403 exp(-14347.2/T); k∞RRKM(T) (1) = 1.664.1012.T0.204 exp(-15465.0/T), k∞RRKM(T) (2) = 1.183.1012.T0.147 exp(-15927.1/T) using TST and RRKM theory, respectively. The pressure-dependent rate constants of isomerization reactions being analysed and solved by RRKM theory and master equation (ME) method were k(T,P) (1) = 9.110.107.P0.815 exp(-4959.3/T) and k(T,P) (2) = 1.382.107.P0.850 exp(-5009.5/T). Our results suggest that, rate constants of both (1) and (2) depend linearly on pressure in the low-temperature and pressure ranges, or in the high-temperature range. Conversely, rate constants of both (1) and (2) are nearly not depending on pressure in the low-temperature and high-pressure ranges. Keywords. Potential energies surface, isomerization reactions, Rice-Ramsperger-Kassel-Marcus theory.